2022
DOI: 10.3389/fimmu.2022.840755
|View full text |Cite
|
Sign up to set email alerts
|

D-Mannose Suppresses γδ T Cells and Alleviates Murine Psoriasis

Abstract: Psoriasis is a chronic skin disorder associated with multiple sequelae, such as psoriatic arthritis and cardiovascular diseases. Increasing evidence has shown that γδ T cells, as sources of IL-17A, play critical roles in psoriatic inflammations. However, there still lack effective ways to manipulate these pathogenic γδ T cells, which are less well studied than αβ T cells. The present study aims to characterize the phenotype of γδ T cells and evaluate the impact of D-mannose (a C-2 epimer of glucose) on γδ T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Moreover, in murine models of psoriasis, the migration of IL-17A-producing cd T cells between skin-draining lymph nodes and the dermis play a critical role in the pathology of psoriasis; 95 furthermore, depletion of cd T cells can alleviate skin inflammation. 96 Collectively, these results indicate that migratory cd T cells function as an important proinflammatory population in the induction of pathology in a variety of diseases. In our study, we observed significantly increased intestinal, cerebral and pulmonary permeability in ISO mice subjected to MCAO.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, in murine models of psoriasis, the migration of IL-17A-producing cd T cells between skin-draining lymph nodes and the dermis play a critical role in the pathology of psoriasis; 95 furthermore, depletion of cd T cells can alleviate skin inflammation. 96 Collectively, these results indicate that migratory cd T cells function as an important proinflammatory population in the induction of pathology in a variety of diseases. In our study, we observed significantly increased intestinal, cerebral and pulmonary permeability in ISO mice subjected to MCAO.…”
Section: Discussionmentioning
confidence: 91%
“…Mannose can upregulate the expression of peroxisome proliferator‐activated receptor γ (PPARγ) and downregulate the growth factor β1 (TGF‐β1) by increasing MR expression, which has anti‐inflammatory and anti‐proliferative effects 36,37 . A recent study revealed that D‐mannose could alleviate the IMQ‐induced psoriasis by suppression of γσT cells, which may be related to the downregulation of AKT/mTOR/HIF‐1ɑ signalling and glycolyic activity 38 …”
Section: Discussionmentioning
confidence: 99%
“…36,37 A recent study revealed that D-mannose could alleviate the IMQ-induced psoriasis by suppression of γσT cells, which may be related to the downregulation of AKT/mTOR/HIF-1ɑ signalling and glycolyic activity. 38…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Transition metal nitrides have attracted great attention because of their low resistance, good mechanical strength and corrosion resistance to various electrocatalytic reactions, such as HER, [21–23] ORR, [24,25] MOR [26–28] and EOR [29,30] . For the MOR and EOR, several transition metal nitrides have been employed as the electrocatalysts and exhibited good catalytic activity and stability [31–35] . For example, Khoshroo et al [31] .…”
Section: Introductionmentioning
confidence: 99%
“…It could be indicated that Ni 3 N showed higher oxidation current density, lower oxidation onset potential and higher stability compared with Ni/C. Li et al [32] . synthesized the NiCu/TiN catalyst by the electrochemical deposition method.…”
Section: Introductionmentioning
confidence: 99%